Restorative approaches for managing dental anomalies - Aljehani, Waleed Abdulrahim; Alsultan, Nouf Abdullah; Altwirki, Abdulaziz Ali; Ibrahim, Abdulrahman Ibrahim; Almutarrid, Mohammed Saud; Alshahrani, Lama Abdullah; Alolayan, Mayada Fahad; Assiri, Manar Ali; Alzahrani, Naif Awdhah; Essa, Afaf Saleh Bu; Faden, Renad Ahmed (International Journal Of Community Medicine And Public Health, 2023)
Dental anomalies, which stem from a complex interplay of genetic and environmental factors during the phases of tooth development, can have multifaceted effects on the appearance, function, and alignment of teeth within the upper and lower jaw. These anomalies are primarily categorized into four main types based on the variations in the number, size, shape, and eruption timing of teeth. They manifest in diverse forms, such as missing teeth, supernumerary teeth, malformed teeth, and irregular tooth positioning. Restorative dentistry serves as a crucial avenue to rectify these anomalies, aiming to not only enhance the functionality but also the aesthetics of affected teeth, thus bolstering the overall oral health and quality of life of patients. It is of particular significance to consider temporary restorative treatments for children with dento-facial abnormalities, not only to address physical concerns but also to mitigate potential psychological trauma and bullying. Additionally, dental anomalies can heighten the susceptibility to dental caries, periodontal diseases, and occlusal irregularities, potentially necessitating intricate and costly dental interventions over time. The research project, initiated on October 12th, 2023, stems from a comprehensive exploration of existing academic literature, encompassing databases such as PubMed, web of science, and Cochrane. Restorative treatment options in modern dentistry offer a comprehensive approach to addressing structural, functional, and aesthetic irregularities in teeth. Prosthodontic solutions, including crowns, bridges, dental implants, and veneers, restore form and function while enhancing aesthetics. Endodontic and operative procedures, such as root canal therapy and dental fillings, preserve teeth, alleviate discomfort, and prevent complications. Orthodontic treatments like braces and Invisalign correct misalignments, improving both function and aesthetics. Surgical approaches, such as orthognathic surgery and impacted tooth removal, are reserved for severe cases. Treatment choices depend on the specific anomaly, emphasizing early intervention for improved oral health and overall well-being.